The Bible's many voices - Carasik, Michael (University of Nebraska Press, 2014)
The most common English translations of the Bible often sound like a single, somewhat archaic voice. In fact, the Bible is made up of many separate books composed by multiple writers in a wide range of styles and perspectives. It is, as Michael Carasik demonstrates, not a remote text reserved for churches and synagogues but rather a human document full of history, poetry, politics, theology, and spirituality. Using historic, linguistic, anthropological, and theological sources, Carasik helps us distinguish between the Jewish Bible's voices-the mythic, the histori.